Connections of Wooden Elements with Steel Rods Glued Into Them Along the Fibers - Nabievich, Ganiev Jahongir; Kakharovich, Atabaev Kadir; Davronovich, Omonov Daler (European Journal of Life Safety and Stability (2660-9630), 2021)
The design solutions of the nodal joints indicate that the joints on the glued rods are found in almost all types of wooden elements: columns, frames, arches. In addition, wooden elements are joined through rods with reinforced concrete or steel elements, while it is possible to note the versatility of the joints on the glued rods. A classified analysis of existing design solutions for nodal connections on glued-in rods is given. Research objectives are formulated.